Incidence of bisphosphonate-related osteonecrosis of the jaw in high-risk patients undergoing surgical tooth extraction - Bodem, Jens; Kargus, Steffen; Eckstein, Stefanie; Saure, Daniel; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2015)
As the most suitable approach for preventing bisphosphonate-related osteonecrosis of the jaw (BRONJ) in patients undergoing surgical tooth extraction is still under discussion, the present study evaluates the incidence of BRONJ after surgical tooth extraction using a standardized surgical protocol in combination with an adjuvant perioperative treatment setting in patients who are at high-risk for developing BRONJ. High-risk patients were defined as patients who received intravenous bisphosphonate (BP) due to a malignant disease. All teeth were removed using a standardized surgical protocol. The perioperative adjuvant treatment included intravenous antibiotic prophylaxis starting at least 24 h before surgery, a gastric feeding tube and mouth rinses with chlorhexidine (0.12%) three times a day. In the follow-up period patients were examined every 4 weeks for the development of BRONJ. Minimum follow-up was 12 weeks. In 61 patients a total number of 184 teeth were removed from 102 separate extraction sites. In eight patients (13.1%) BRONJ developed during the follow-up. A higher risk for developing BRONJ was found in patients where an additional osteotomy was necessary (21.4% vs. 8.0%; p = 0.0577), especially for an osteotomy of the mandible (33.3% vs. 7.3%; p = 0.0268). Parameters including duration of intravenous antibiotic prophylaxis, the use of a gastric feeding tube and the duration of intravenous BP therapy showed no statistical impact on the development of BRONJ. Furthermore, patients currently undergoing intravenous BP therapy showed no higher risk for BRONJ compared with patients who have paused or completed their intravenous BP therapy (p = 0.4232). This study presents a protocol for surgical tooth extraction in high-risk BP patients in combination with a perioperative adjuvant treatment setting, which reduced the risk for postoperative BRONJ to a minimum. However, the risk for BRONJ increases significantly if an additional osteotomy is necessary, especially in the mandible.